lntra and post-operative handling of surgical poor risk patients - Voelker, Ricardo; Bagattini, Juan Carlos; Balboa, Oscar; Cassinelli, Nilda; Correa, Humberto; Tamborindeguy, Luis (Cirugía del Uruguay, 1984)
The problem of poor risk surgical patients is focused with a dynamic approach by a multidisciplinarian team where the surgeon acts as a coordinator.